2018
DOI: 10.1038/s41598-018-25769-y
|View full text |Cite
|
Sign up to set email alerts
|

Her2 Ile655Val polymorphism and its association with breast cancer risk: an updated meta-analysis of case-control studies

Abstract: Breast cancer (BC) is one of the most common types of cancer in women worldwide. Several factors including genetic and environmental have been linked with susceptibility to development of BC. Her2 is a transmembrane protein with tyrosine kinase activity, overexpressed in several cancers including BC. Various studies in different populations have shown association of Her2 variants with susceptibility to BC, however these results were inconsistent, inconclusive and controversial. To obtain a common conclusive fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 71 publications
1
15
0
Order By: Relevance
“…Heterogeneity among the studies and publication bias were calculated using Begg's funnel plots and chi-squared-based Cochran's Q tests, respectively. Egger's regression tests were performed to analyze and measure the symmetry of funnel plots, as described previously [22]. Asymmetrical funnel plots were made symmetrical using the "Trim and Fill" method.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Heterogeneity among the studies and publication bias were calculated using Begg's funnel plots and chi-squared-based Cochran's Q tests, respectively. Egger's regression tests were performed to analyze and measure the symmetry of funnel plots, as described previously [22]. Asymmetrical funnel plots were made symmetrical using the "Trim and Fill" method.…”
Section: Resultsmentioning
confidence: 99%
“…Baxter et al found that the TGF-β1*6A variant increased BC risk by 60% [21]. However, contradictory results have also been observed [19,[22][23][24][25]. Therefore, we performed the current meta-analysis to provide conclusive evidence for the associations between TGF-β1 polymorphisms and BC risk.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Estrogen is a considerable regulator of mammary gland growth and differentiation, and it is also key in the occurrence and development of breast cancer [ 42 ]. Furthermore, studies have shown that excessive endogenous and endogenous estrogens may lead to pathological changes in many cancer cell lines, including breast cancer cells [ 43 ]. Therefore, as a gene encoding estrogen receptor, the genetic variation of ESR1, may expose the potential risk of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Singla et al [49] found, among patients in Indian hospitals, a positive significant association between HER2 I655V and the susceptibility of developing breast cancer, while other authors have detected negative correlation when examining patients in Brazil [66]. A metaanalysis conducted in 2019 [67] revealed the impacts of ethnicity on the association between mutation HER2 I655V and breast cancer risk, observing positive correlation in Asia and Africa but not the other continents. e relationship between this mutation and the response to trastuzumab-containing chemotherapy in HER2-positive breast cancer patients has been examined, yet results have been contradictory.…”
Section: Mutations In the Transmembrane Domainmentioning
confidence: 98%